2016
DOI: 10.1039/c6cp05010g
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and association of ions in aqueous solutions: the case of imidazolium based ionic liquids

Abstract: The mobility and the mechanism of ion pairing of 1,1 electrolytes in aqueous solutions were investigated systematically on nine imidazolium based ionic liquids (ILs) from 1-methylimidazolium chloride, [MIM][Cl], to 1-dodecyl-3-methylimidazolium chloride, [1,3-DoMIM][Cl], with two isomers 1,2-dimethylimidazolium chloride, [1,2-MMIM][Cl], and 1,3-dimethylimidazolium chloride, [1,3-MMIM][Cl]. Molecular dynamics (MD) simulations, statistical mechanics calculations in the framework of the integral equation theory u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 80 publications
1
26
0
Order By: Relevance
“… [119] or MD simulation studies in ref. [120] , [121] , respectively. Box side lengths of 80 Å for all systems were used to define the system dimensions.…”
Section: Methodsmentioning
confidence: 99%
“… [119] or MD simulation studies in ref. [120] , [121] , respectively. Box side lengths of 80 Å for all systems were used to define the system dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, values of Λ° decrease with increasing alkyl chain length of the imidazolium chloride ILs (from b to j) in water medium. [76] From Table 1. it can be seen that K A values for presented ILs are biggest in DCM, [81] 1-BuOH, [75,83] 1-PrOH, [82,83] and 2-PrOH.…”
Section: Some Recent Conductometric Volumetric and Viscometric Results For Imidazolium-based Ionic Liquids In Various Solventsmentioning
confidence: 99%
“…[85] Weak ion association is present in DMSO, [86] and in W solvent. [76][77][78] These results suggest that the imidazolium cation and anions of ILs are less associated or fully disociated in the solvent, which possesses a high relative permittivity due to the independent solvation od ions. One of the important factors affecting the ionic association is the ion-solvent interaction.…”
Section: Some Recent Conductometric Volumetric and Viscometric Results For Imidazolium-based Ionic Liquids In Various Solventsmentioning
confidence: 99%
“…Meanwhile, in [24], it was shown that ionization of the IL leads to the decrease of viscosity of the studied systems. The dissociation constant of IL [C 6 Meim]Cl (0.385 mol/L), as well as the diffusion coefficient of [C 6 Meim] + cation (7.65 × 10 −6 cm 2 /s), were estimated in [25] for infinitely diluted aqueous solutions. A nearly 10-fold lower diffusion coefficient was measured in [26] for pure IL [C 2 Meim][NTf 2 ] with NMR spectroscopy: 3 × 10 −7 cm 2 /s to 9 × 10 −7 cm 2 /s, depending on the temperature and applied electric field.…”
Section: Introductionmentioning
confidence: 99%